Characterizing Soil Dissolved Organic Matter Across a Permafrost Thaw Gradient (Continuous to Isolated Patches) in Northeastern China - Siyuan Zou; Xiaodong Wu; Jiawei Zhang; Nannan Zhang; Xiangwen Wu; Shuying Zang (Ecology and Evolution, 2025)
ABSTRACT Permafrost zones are currently experiencing rapid warming, and dissolved organic matter (DOM) is a potentially important pathway for carbon release from permafrost after thawing. In this study, based on the UV–Vis spectral data and parallel factor analysis of fluorescence excitation‐emission matrix (EEM) spectrophotometry, we investigated the source and composition of DOM at different thawing stages in the permafrost zone of Northeast China. The results indicate that there are significant differences in the content of soil dissolved organic carbon (DOC) among different types of permafrost zones (continuous permafrost: 143–347 mg/kg, discontinuous permafrost 172–462 mg/kg, isolated patches permafrost 195–610 mg/kg), and the permafrost types had a significant effect on soil DOC (p < 0.05). Five fluorescent components were identified from all samples, including four humic acid‐like substances (C1, C2, C3, C4) and one tryptophan‐like substance (C5). The proportion of C5 in the deep layer of the sporadic patch permafrost area (55.39%) is about 49% higher than that in the continuous permafrost area (37.25%). With increasing soil depth, the characteristics of DOM transition from high DOC value, high aromaticity, high molecular weight, and plant origin to low DOC value, low aromaticity, low molecular weight, and microbial origin. The results of soil DOM component analysis indicate that the content of C5 significantly increases (p < 0.01) in the deeper layers of isolated patch permafrost. With the change of permafrost types, the risk of DOM decomposition may increase. These findings contribute to a deeper understanding of the dynamics and stability of DOM in permafrost under environmental warming, as well as its biogeochemical impacts in natural environments.